Costs of Environmental Degradation in the Mountains of Tajikistan - World Bank (World Bank, Washington, DC, 2021)
Rural livelihoods in Tajikistan heavily rely on natural resources and the agriculture sector. A large proportion of the rural population depends on agriculture, and weather-related calamities are exerting increasing pressure on natural resources and agricultural sectors, the major contributors to Tajikistan's gross domestic products (GDP.) The resulting environmental degradation has taken a significant toll on the economic and sustainable development of the country. Despite the significant importance of the issue for Tajikistan's current and future economic growth, the negative effects of environmental degradation are missing from the country's economic analysis and government priorities, and are not considered in its medium-term macro projections. In order to address these concerns, the overall objective of this study is to enhance the understanding of the economic costs of environmental degradation, and to promote improved management and planning at national and subnational levels in Tajikistan.